The Methodology of Saudi Critical Authorship - Khaleel, Widad Kadhim; Al-Baldawi, Hassan Jaafar Sadiq (Journal of Ecohumanism, 2024)
Methodology is among the most crucial tools for both general linguistic composition and critical analysis. Every classification system requires a methodology to determine how its categories are selected and its contents are organized. Methodology refers to the specific approach appropriate for each science or topic within that science. It consists of a set of general rules designed to uncover the truth in a field of study. Essentially, it is the approach that a researcher uses to explore a problem, discover the truth, or achieve the desired objective.